Resisting eviction: the polymorphy of peripheral spatial politics in Brazil. Issue 3 (27th May 2022) - Albert, Victor
ABSTRACT: Struggles against eviction are key moments in the (re)production of informal housing in Brazilian cities, as they contest the uprooting and displacement of generally low-income families. While recent research has focused on displacement due to the World Cup and Olympic Games mega-events, this paper explores struggles against eviction that are less high profile, underscoring the distributed nature of evictions in processes of urban change. Drawing on long term fieldwork, this paper examines three cases of struggles against eviction in different cities in the southeast of Brazil. This comparison highlights the everyday contestations that take place across varied geo-political terrain; the morphological constraints and opportunities for collective action of building as opposed to land occupations; the punitive and cooperative state logics with which threatened communities must engage; and drawing on recent attempts in geography to combine theorisations of territory, place, network and scale, contributes to understanding the polymorphy of spatial struggles in contemporary Brazil.